2012
DOI: 10.1017/s0963548312000351
|View full text |Cite
|
Sign up to set email alerts
|

On Sums of Generating Sets in ℤ2n

Abstract: Let A and B be two affinely generating sets of Z n 2 . As usual, we denote their Minkowski sum by A + B. How small can A + B be, given the cardinalities of A and B? We give a tight answer to this question. Our bound is attained when both A and B are unions of cosets of a certain subgroup of Z n 2 . These cosets are arranged as Hamming balls, the smaller of which has radius 1.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…A sequence of papers [25,62,39,45,29] established this conjecture for torsion r = 2, (i. e., to the groups G = F n 2 ) with C = 2, and Even-Zohar and Lovett [30] extended it to any prime torsion, also with C = 2. Theorem 2.9 (Even-Zohar and Lovett).…”
Section: Conjecture 28 (Ruzsa)mentioning
confidence: 95%
“…A sequence of papers [25,62,39,45,29] established this conjecture for torsion r = 2, (i. e., to the groups G = F n 2 ) with C = 2, and Even-Zohar and Lovett [30] extended it to any prime torsion, also with C = 2. Theorem 2.9 (Even-Zohar and Lovett).…”
Section: Conjecture 28 (Ruzsa)mentioning
confidence: 95%
“…For p = 2 and v = e i , the compression operator C v coincides with C {i} as in [8,6]. Compressions along general multidimensional subspaces can be defined analogously, but are not necessary for this work.…”
Section: Compressions Inmentioning
confidence: 99%
“…In particular, Green and Tao [8] showed that F (2, K) ≤ 2 2K+O( √ K log K) , thus settling Conjecture 2 for r = 2. A refinement of their argument enabled the first author [6] to find the exact value of F (2, K), which turned out to be Θ(2 2K /K). In this note we extend these techniques to the case of general prime torsion.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations